The Impact of Source Credibility of Live-Streaming Celebrities on Consumers’ Impulse Buying Behavior in Live E-Commerce: A Stimulus-Organism-Response Perspective - Kun, Huang (International Review of Management and Marketing, 2026)
The study uses the Stimulus-Organism-Response Model to examine how live celebrity source credibility affects consumers’ impulse buying behavior in live streaming e-commerce. The study treats the trustworthiness, expertise, and attractiveness of live celebrities as external stimuli, parasocial interaction and flow state as consumers’ internal psychological states, and impulse buying behavior as the final behavioral response, while collecting data through online questionnaire surveys. The findings show that trustworthiness and expertise significantly and positively affect consumers’ parasocial interaction and flow state; attractiveness has a significant positive effect on flow state, but its effect on parasocial interaction is not significant. Parasocial interaction not only significantly promotes flow state but also positively influences consumers’ impulse buying behavior. Flow state also significantly promotes consumers’ impulse buying behavior. These findings indicate that impulse buying in live streaming e-commerce is not solely driven by product information or promotional stimuli, but is formed through interaction and immersive experience between consumers and live celebrities. This study extends source credibility theory and the Stimulus-Organism-Response Model in live streaming e-commerce research, while offering practical implications for live streaming e-commerce platforms, brand merchants, and live celebrities in anchor selection, content design, and interactive strategy optimization.